Aided phytostabilization of copper contaminated soils with ?L. perenne? and mineral sorbents as soil amendments = Wspomagana fitostabilizacja gleby zanieczyszczonej miedzią z wykorzystaniem L. Perenne i sorbentów mineralnych jako dodatków - Radziemska, Maja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present study was designed to assess phytostabilization strategies for the treatment of soil co-contaminated by increasing levels of copper with the application mineral amendments (chalcedonite, zeolite, dolomite). From the results it will be possible to further elucidate the benefits or potential risks derived from the application of different types of mineral amendments in the remediation of a copper contaminated soil.
Keywords: aided phytostabilization; contaminated soils; risk minimization; Lolium perenne L.; fitostabilizacja; zanieczyszczenie gleby; metale ciężkie; minimalizacja ryzyka